Prophylactic Efficacy of Tai Chi on Migraine Attack: Study Protocol of a Pilot Randomized Controlled Trial. (December 2016) - Xie, Y.J.; Hui, S.-C.; Ho, S.C.; Suen, L.K.P.
Abstract : Background: People with repeated migraine attacks are pain and personal suffering, have impaired social and personal life. Regular exercise is recommended for preventing migraine attack in the literature. As a body-mind exercise, Tai Chi's potential therapeutic efficacy on the prophylaxis of migraine remains largely unknown. Objective: To test the effects of a12-week Tai Chi training on the prophylaxis of episodic migraine in Chinese women, and to evaluate the feasibility, acceptability, compliance and maintenance of Tai Chi exercise among this population. Methods: A two-arm individual level randomized controlled trial is designed. Local women diagnosed with episodic migraine between 18–65 years will be randomly assigned to one of two groups: 1) a Tai Chi training (1 hour per day, 5 days per week); or 2) a waiting list control group. The control group will receive a "delayed" Tai Chi training at the end of the trial. A total of 70 participants will be randomized and the intervention period will be 12 weeks with another 12-week follow-up. Number of attacks per month (frequency of attack), intensity and duration of headache, stress, sleep quality and quantity, fatigue, Health-related Quality of Life, and body composition will be measured at baseline and at 12 weeks and 24 weeks. The main outcomes are the difference in frequency of attack from baseline to the 12 weeks and 24 weeks after randomization, and the proportion of patients with at least a 50% reduction of the number of attacks per month. The intervention effect will be estimated by calculating the differences of outcomes from baseline to the end of the trial between the intervention and control groups using intention-to-treat analysis. Conclusion: Given the importance of reducing attack impacts in migraine sufferers, the findings of this pilot study will provide new insights regarding the role of Tai Chi intervention in migraine prophylaxis.